Efektivitas Konseling Kelompok Teknik Self-Management untuk Meningkatkan Self-Regulated Learning Siswa di SMP Negeri 2 Sukodono - Khasanah, Nur; Mufidah, Elia Firda (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
This research aims to determine the effectiveness of group counseling using self-management techniques to increase students' self-regulated learning at SMPN 2 Sukodo. The research population was class VIII students and sampling used a purposive random sampling technique and obtained a total of 6 students. This research uses quantitative research methods with a one group pre-test post-test design. Data collection uses a self-regulated learning scale developed by researchers. The data analysis using Wilcoxon UI using SPSS. The research results show the value of Asymp. Sig (2-tailed) of 0.027. It's smaller than <0.050, which means nol hypothesis is rejected. Based on this results shows that Self-Management Techniques in Group Counseling are effective in increasing students' self-regulated learning at SMP Negeri 2 Sukodono.